MaCGE-MOD: Malta's computable general equilibrium model - Ian P. Cassar; Nathaniel Debono; Stefano Deriu; Rosita Pretaroli; Noel Rapa; Francesca Severini; Claudio Socci (Central Bank of Malta, 2023)
This paper introduces the latest addition to the modelling toolkit of the Central Bank of Malta: a static Computable General Equilibrium model for Malta named MaCGE-MOD. Developed through a collaboration with the University of Macerata, the model is a multiinput, multi-output and multi-sector model, calibrated on a Social Accounting Matrix which illustrates the income flows among production processes and institutional sectors in Malta. The model constitutes a set of equations which describe the circular flow of income in the economy and the behaviour of economic agents. It is a useful tool to determine ex ante the impacts of policy decisions or exogenous shocks once all the associated direct, indirect and induced effects have propagated through the economy. As it is based on a Social Accounting Matrix, the model can provide disaggregated sectoral analyses to complement analyses of the aggregate effects of policy-making scenarios or exogenous shocks. Thus, MaCGE-MOD can potentially be an important tool for policy makers to identify effects not easily discernible from the other aggregated models currently available.
Keywords: C61; C68; D58; E16; E17; H30; 330; Computable General Equilibrium; Social Accounting Matrix; Malta; simulations; sectoral analyses